Commentary on "Multisensory rooms: essential characteristics and barriers to effective practice". Issue 2 (6th May 2020) - Challis, Ben; Hildred, Mark; Bailey, Jennie Ruth
Abstract : Purpose: The purpose of this paper is to provide a commentary on Grace's article on multisensory rooms. Design/methodology/approach: This paper gives a historical overview of the emergence and evolution of multi-sensory environments (MSEs) together with an outline of a current research project seeking to support best practice. Findings: MSEs have become a standard feature in special educational needs schools in the UK with government building guidelines now stipulating the inclusion of at least one sensory room within any such provision. However, there is little research-based evidence from which design decisions can be informed. Instead, previous research has tended to focus on the effectiveness of MSEs for specific user groups. Originality/value: The outlined research will establish some initial design principles for MSEs.